The potential of ingestible sensors combined with family involvement interventions for medication supervision in Tuberculosis patients: A literature review - Meidina, Adinda Nezma; Ramadhanti, Nafilah; Riza, M. Aidil Tarensyah; Dapala, Zelka; Fareza, M. Daffa (Public Health Risk Assesment Journal, 2025)
Background: Tuberculosis (TB) is an airborne infectious disease that remains the second leading cause of death from infectious diseases globally. A major challenge in eliminating TB, despite it being preventable and curable, is the low adherence to treatment. This literature review aims to provide insights into the potential of ingestible sensors combined with family involvement interventions for medication supervision in TB patients, ensuring that medications are actually swallowed and addressing a key limitation of the previous DOT method. Methods: This study used a literature review method with the keywords "family engagement intervention", "digestible sensor", and "tuberculosis [MeSH]" to search databases such as Google Scholar, Science Direct, ResearchGate, and NCBI. Inclusion criteria included in vitro and in vivo experimental studies, cohort studies, comparative analysis studies, and reviews published in the last 10 years. Exclusion criteria included incomplete studies, inaccessible papers, and non-English/Indonesian texts. After applying these criteria, 35 journals and 1 book were selected for review and analysis. Findings: Ingestible sensors have shown over 80% effectiveness in monitoring medication adherence by providing real-time data for precise treatment adjustments. When combined with family involvement, these interventions address psychosocial barriers like stigma and lack of support, further improving adherence. This synergy significantly reduces non-compliance, prevents drug resistance, and enhances treatment outcomes for TB patients. Conclusion: Ingestible sensors combined with family involvement offer a more effective approach to TB treatment by ensuring medication is swallowed and providing psychosocial support, reducing risks of transmission, relapse, and drug resistance. However, equitable access and adequate infrastructure, supported by government and societal cooperation, are crucial for the successful implementation of this system globally. Novelty/Originality of this article: This study explores the innovative use of ingestible sensors combined with family involvement to improve TB treatment adherence, offering a novel contribution to TB management.